Correlation of Age, Tumor Size, and Histopathological Type with Indicator Tumor Progression of Penile Squamous Cell Carcinoma in Bali - Astuti, Ni Luh Putu Vina Juni; Lestari, Desak Putu Oki; Sari, Ni Luh Putu Eka Kartika; Armerinayanti, Ni Wayan; Evayanti, Luh Gde; Perdana, I Gede Sukma Okta (Indonesian Journal of Cancer, 2025)
Background: Penile cancer is a rare malignancy globally, but Bali accounts for approximately 40% of Indonesia’s cases. Age, tumor size, and histopathological type are recognized factors influencing penile cancer progression, with grade, depth of invasion, lymph node metastasis, and distant metastasis serving as key indicators. However, the prognostic value of these factors, particularly depth of invasion, remains debated. This study aimed to evaluate the correlation between age, tumor size, and histopathological type with indicators of tumor progression in penile squamous cell carcinoma (SCC) in Bali.Method: A cross-sectional analytical study was conducted on 160 cases of penile SCC. Dependent variables included tumor grade, depth of invasion, and lymph node metastasis, while independent variables were age, tumor size, and HPV status (inferred from histopathology). Age was categorized as 60 or ≥60 years, tumor size as 4 cm or ≥4 cm, and depth of invasion as T1–T4. Multivariate analysis using the chi-square test was performed to assess associations.Results:  Most patients were aged ≥ 60 years, had HPV-independent SCC, tumor size ≥ 4 cm, grade 2 tumors, and T1 depth of invasion, with lymph node metastasis observed in a minority. Multivariate analysis revealed significant correlations between age, tumor size, and histopathological type with grade (p = 0.026, R² = 0.056), depth of invasion (p 0.001, R² = 0.445), and lymph node metastasis (p = 0.004, R² = 0.075). Tumor size demonstrated the strongest association with depth of invasion (OR = 9.618, p 0.001) and lymph node metastasis (OR = 6.846, p 0.001).Conclusion: Tumor size is a significant predictor of both depth of invasion and lymph node metastasis in penile SCC. Clinical assessment of tumor size should be emphasized as a key prognostic factor to guide early intervention strategies in patients with penile SCC in Bali.